Oposisi Biner dalam Serat Menak Kanin Karya R.Ng.Yasadipura I - Ameliya, Dina; Nugroho, Yusro Edy (Universitas Lampung, 2024)
Serat Menak Kanin tells the story of Wong Agung's struggle in the war between Muslims and Infidels which is divided into fourteen episodes with the ending of Umarmaya's death caused by Dewi Kalajohar. Serat Menak Kanin is a Javanese literary work built on the basis of a mixture of Javanese and Arabic culture. Serat Menak Kanin is a Javanese literary work that originates from an Arabic story and was adapted into a Javanese story. This story comes from the Hikayat Amir Hamzah which originates from Persia and is set out in a Javanese setting and language. Menak Kanin fiber, which is a product of a mixture of two cultures, allows it to be studied from a binary opposition perspective. The problem of this research is how the cultural reconstruction that occurs in Serat Menak Kanin involves two cultural poles, namely Arabic and Javanese. The aim of this research is to describe the form of mixing of two cultures in the realm of hybridity and mimicry. This research uses a literary sociology approach with postcolonial theory. The research method used is a qualitative descriptive method by analyzing the Serat Menak Kanin text as a whole and recording data that includes hybridity and mimicry. The results of this research show that Serat Menak Kanin is dominated by a binary opposition relationship in the form of hybridity by combining two cultural backgrounds in the names of characters in stories such as Raden Kanjun. Meanwhile, binary opposition in the form of mimicry is found in the use of Arab settings and the Perang Gebyah.Keywords: Binary Opposition, Postcolonial, Hybridity, Mimicry, Serat Menak Kanin